2018
DOI: 10.5455/medscience.2018.07.8806
|View full text |Cite
|
Sign up to set email alerts
|

The role of tubes with preservative in urinalysis of pregnant women

Abstract: In order to increase the efficiency of the preanalytical process at the Public Health Laboratory (PHL) where urinalysis is performed on pregnant women admitted at primary care family health centres (FHC), our aim was to demonstrate the efficacy of preservative urine tubes in this study. The first morning urine samples of 84 pregnant women were collected into urine tubes with or without preservative. The first analysis was used as a reference. The tubes with preservative containing chlorhexidine were transporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
1
0
0
Order By: Relevance
“…In their study conducted with 84 samples, Avcı et al found that tubes containing chlorhexidine as a preservative and transported more than two hrs yielded unaffected results for all parameters within the same day [17]. Ekşioğlu et al reported comparable results to our study.…”
Section: Discussionsupporting
confidence: 83%
“…In their study conducted with 84 samples, Avcı et al found that tubes containing chlorhexidine as a preservative and transported more than two hrs yielded unaffected results for all parameters within the same day [17]. Ekşioğlu et al reported comparable results to our study.…”
Section: Discussionsupporting
confidence: 83%